Development of a MST sensor probe, based on a SP3T switch, for biomedical applications. Issue 1 (8th August 2020) - Donelli, Massimo; Manekiya, Muhammedhusen; Iannacci, Jacopo
Abstract: Recently wireless sensors based on modulated scattering techniques (MST) have been applied to different practical scenarios demonstrating their capabilities. A particular configuration of the MST sensor antenna permits to retrieve the electric characteristics of the media which surround the antenna tag. Thanks to the capability of MST probes to retrieve the dielectric characteristics of the surrounding media, MST probes can be applied efficiently for biomedical applications. The development of MST sensors working at microwave frequency bands require the development of suitable and expensive RF switches, to avoid this problem RF‐MEMS microwave switches could be considered. In this work the use of a customized SP3T MEMs for MST probes has been considered. Thanks to the MEMs switch an MST probe can be developed considering reduced dimensions, complexity, and good performances up to high frequency bands. In particular, an MST system able to transmit data and the dielectric characteristics of the surrounding media through a wireless channel has been designed, fabricated, and experimentally assessed. The obtained experimental results demonstrated the capabilities of MST probes as miniaturized biomedical sensors.